A Health and Safety Model for Occupational Exposure to Radiofrequency Fields and Static Magnetic Fields from 1.5 and 3 T MRI scanners - Rathebe, P.; Weyers, C.; Raphela, F. (Health and Technology volume, 2019)
The exposure ofMRI staff to SMFs and RF fields in theMRI units happen as a result of their induced movement in theMRI room during patients’ examination. Exposure to SMFs among health care workers has been associated with vertigo, nausea, increased heart rate, hypothermia and metallic taste in the mouth. The only known adverse effects associated with RF fields’ exposure include induced tissue heating, and the scientific arguments regarding non-thermal effects are inconclusive. The emission of MRI-related electromagnetic fields and exposure of workers to RF energy and SMFs can be reduced through implementation of reasonably practicable control measures. This study attempts to recommend the hierarchy of controls that can be implemented in the MRI units to reduce emissions and exposure of MRI staff to RF energy and SMFs. The controls are recommended based on exposure assessment conducted to quantify the exposure levels and self-reported priori-related and unrelated health consequences. In the MRI units, elimination is an impractical measure, hence, the implementation of engineering and administrative control measures as well as the utilisation of personal protective equipment (PPE) are recommended to mitigate exposure. Engineering controls include modification of MRI scanners to reduce emissions while administration controls include the design of work schedules and processes to be adaptive by MRI staff. PPE is recommended as a last resort and include protective equipment that are fit to reduce exposure arriving to workers. In South Africa, there is no legislation to assist in enforcing exposure limits and as a result, exposure levels are not monitored. The model of this kind could assist in reducing exposure levels in the MRI units and substantially reduce exposure-related effects amongst workers.
Original Paper
Keywords: Health and Safety; Occupational Exposure; Model; SMFs; RF Energy